1991
DOI: 10.1128/jb.173.22.7070-7076.1991
|View full text |Cite
|
Sign up to set email alerts
|

Novel insertion sequence IS1380 from Acetobacter pasteurianus is involved in loss of ethanol-oxidizing ability

Abstract: Acetobacter pasteurianus NCI1380, a thermophilic strain isolated from the surface culture of acetic acid fermentation, showed genetic instability to produce at high frequency spontaneous mutants which were deficient in ethanol oxidation because of the loss of alcohol dehydrogenase activity. Southern hybridization experiments with the cloned alcohol dehydrogenase-cytochrome c gene cluster as the probe showed insertion of an unknown DNA fragment into a specific position in the cytochrome c gene in most of the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 17 publications
2
62
0
1
Order By: Relevance
“…20 23) In all experiments so far described in this paper, bacterial growth was followed by reading the turbidity of the culture medium as a reference to cell number. As has been reported by Takemura et al,24) it must be noted that the turbidity does not mean the total viable cells. Different from those used by Takemura et al,24) the acetic acid bacteria used in this study were always exposed to acidic conditions, at least, in the presence of 1 % acetic acid.…”
Section: Effects Of Initial Concentrations Of Acetic Acid and Elhanolmentioning
confidence: 64%
See 1 more Smart Citation
“…20 23) In all experiments so far described in this paper, bacterial growth was followed by reading the turbidity of the culture medium as a reference to cell number. As has been reported by Takemura et al,24) it must be noted that the turbidity does not mean the total viable cells. Different from those used by Takemura et al,24) the acetic acid bacteria used in this study were always exposed to acidic conditions, at least, in the presence of 1 % acetic acid.…”
Section: Effects Of Initial Concentrations Of Acetic Acid and Elhanolmentioning
confidence: 64%
“…As has been reported by Takemura et al,24) it must be noted that the turbidity does not mean the total viable cells. Different from those used by Takemura et al,24) the acetic acid bacteria used in this study were always exposed to acidic conditions, at least, in the presence of 1 % acetic acid. The viable cell count experiments during the culture showed a good accordance Fermentation period (h) Fermentation period (h) A. rancens SKU 1111 was incubated i'l a medium containing 3% acetic acid as carbon and energy sources.…”
Section: Effects Of Initial Concentrations Of Acetic Acid and Elhanolmentioning
confidence: 64%
“…It cannot be accepted that the turbidity means the total viable cells. As has been reported by Takemura et al,22) it must be noted that the majority of the cells began to die in the stationary phase after ethanol was exhausted and acetic acid accumulated to the maximal level.…”
Section: Vinegar Fermentation Under Static Culturementioning
confidence: 73%
“…It can be readily expected that ADH and ALDH activities go down and lose their physiological roles when ethanol is consumed from the culture medium. Alternatively, the decrease in specific activities of ADH and ALDH in the prolonged culture would reflect the predominated increase of ADH deficient mutants as reported by Takemura et al 22 ) They found a novel insertion sequence, IS 1380, which causes a genetic instability that produces spontaneous ADH deficient :r3~8~O~C--------~~=O==~ To I liter of sake mash medium containing I % acetic acid, ethanol was added to 5% and vinegar fermentation was done at 30°C for the period as indicated under static conditions. Every two days, acetic acid accumulated (0), bacterial growth (.…”
Section: Vinegar Fermentation Under Static Culturementioning
confidence: 99%
“…IS1380 from the acetic acid bacterium A. pasteurianus causes a loss of ethanol oxidation activity by insertion into the cytochrome c gene. 12) IS1427, which also belongs to the IS1380 family, from the 1,2-dibromoethane-degrading bacterium Xanthobacter autotrophicus GJ10, confers monobromoacetate resistance on it by insertion to a site proximal to dhlB encoding a haloacid dehalogenase, resulting in overexpression and mobilization to a plasmid of dhlB.…”
mentioning
confidence: 99%